Prediction of Ecosystem Service Value (ESV) Based on Grey System Theory Model: A Case Study of Hanzhong City - Feng, Yan; Said, Fathin Faizah; Salleh, Norlida Hanim Mohd; Radzi, Naziatul Aziah Mohd; Li, Yunqiao (Journal of Ecohumanism, 2024)
Ecosystem services play an important role in human survival and development. The prediction and evaluation of ecosystem service value (ESV) can provide scientific basis and guidance for the protection and restoration of the ecosystem, and provide decision-making support for policy formulation and resource allocation. It has significant practical and long-term significance, and is an important means to promote the construction of ecological civilization and sustainable development. Taking Hanzhong City, Shaanxi Province, China as an example, based on the land use data from 2010 to 2020, this paper analyzes the temporal and spatial evolution of the ESV in Hanzhong City, and uses the grey system theory model to forecast and analyze the ecosystem value in the region from 2025 to 2030. The results show that: (1) The main land-use types in Hanzhong are grassland, forestland and farmland. From 2010 to 2020, the area of farmland, water area and grassland decreased, while the area of forestland, built-up land and barren land increased. (2) From 2010 to 2020, the ESV of Hanzhong City showed a trend of decreasing first and then increasing, and Zhenba County had the highest proportion of increasing ESV. From the perspective of different ecosystem service types, the value provided by soil conservation service is the largest, while the value provided by water supply service is the least. From the perspective of different land use types, the value provided by forestland is the largest, and the value provided by built-up land is the least. (3) It is predicted that the ESV in Hanzhong will continue to increase from 2025 to 2030, but due to the insufficient protection of water sources and the expansion of built-up land, the ESVs in some regions will decrease year by year. The future planning of Hanzhong should pay attention to the coordinated development of a new urbanization process and ecological civilization construction to build a green ecological city.Ecosystem service value (ESV);